Auditory Brainstem Responses in Tinnitus: A Review of Who, How, and What? - Milloy, Victoria; Fournier, Philippe; Benoit, Daniel; Noreña, Arnaud; Koravand, Amineh (Frontiers in Aging Neuroscience, 2017)
The auditory brainstem response (ABR) in tinnitus subjects has been extensively investigated over the last decade with the hope of finding possible abnormalities related to the pathology. Despite this effort, the use of the ABR for tinnitus diagnosis or as an outcome measure is under debate. The present study reviewed published literature on ABR and tinnitus. The authors searched PubMed, MedLine, Embase, PsycINFO, and CINAHL, and identified additional records through manually searching reference lists and grey literature. There were 4566 articles identified through database searching and 151 additional studies through the manual search (4717 total): 2128 articles were removed as duplicates and 2567 records did not meet eligibility criteria. From the final 22 articles that were included, ABR results from 1240 tinnitus subjects and 664 control subjects were compiled and summarized with a focus on three main areas: the participant characteristics, the methodology used and the outcome measures of amplitude and/or latency of waves I, III and V. The results indicate a high level of heterogeneity between the studies for all the assessed areas. Amplitude and latency differences between tinnitus and controls were not consistent between studies. Nevertheless, the longer latency and reduced amplitude of wave I for the tinnitus group with normal hearing compared to matched controls was the most consistent finding across studies. These results support the need for greater stratification of the tinnitus population and the importance of a standardized ABR method to make comparisons between studies possible.